(untitled) (Nexus International Journal of Science and Education, 2024)
This study explored the experiences of home ecomomics teachers in strengthening the life skills of the leaners, specifically in Cluster 13, Paquibato District, Davao City. There were eight (8) home economics teachers who participated in the study. This study made use of a phenomenological approach to extract the ideas of the parent participants. The participants were purposely selected as representatives from the group of HE elementary schools in the same division. The virtual in-depth-interview was employed to gather some information as regards to their respective experiences. Using the thematic analysis, the following themes emerged as pertains to the experiences and views of the participants: Practicing good communication, strengthening food preparation techniques and guided and appropriate decision making. The coping mechanisms of HE teachers in enhancing the life skills of the students were: building students’ capacity, opening to feedback and focusing on basic life skills for the 21st century. The insights drawn from the participants were: understanding the millennial characteristics and enhance practical life skills. The teachers may be more sensitive to the needs of the learners and be watchful on the skills of the leaners. These teachers may consider the personal characteristics of the learners. The home economics learners may be guided properly to enrich their knowledge in home economics and improve their skills in cooking but being more knowledgeable on how to live and be healthy.